Modeling and simulation of liquid fertilizer devices for nitrogen top dressing in maize fields - Silva, Marcelo José da; Correa, Murilo Henrique Ferreira; Reis, Sérgio Luiz Saraiva dos (Acta Scientiarum. Agronomy, 2026)
Nitrogen top dressing is essential to supplement maize needs in crop fields. In Brazilian agriculture, a spreader is the most popular equipment used to apply nitrogen fertilizer to growing maize. However, spreaders present at least three problems: non-uniform fertilizer placement, granular fertilizer placement on the top of maize leaves, and granular fertilizer scattering without a precise target. As an alternative, liquid nitrogen fertilizer applied in side bands of maize rows can improve nutrient placement and dosage precision. The objective was to design a liquid fertilizer application device for assembly on a boom sprayer. For this, a programming model was simulated in Matlab. The liquid fertilizer source, fertilizer rate, maize row width, and boom sprayer speed were considered as input parameters. The simulation assisted in the design of the liquid fertilizer device. The device was constructed and evaluated on a laboratory bench. As a result, pressure, nozzle outlet flow, and forward speed were compatible with a self-propelled sprayer. The proposed process showed the potential to improve the outlet flow quality (coefficient of variation less than 10%). In addition, the liquid fertilizer device was considered simple to assemble in the sprayer’s boom. These characteristics could represent some attractive aspects for the farmers.